2016
DOI: 10.1210/jc.2016-1646
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Events Predict Adult Testicular Function; Data Derived From the Western Australian (Raine) Birth Cohort

Abstract: Exposures to maternal smoking and higher cord blood estrogens at delivery were associated with a reduced sperm output in adulthood. Optimal adult testicular function depends on being born at or above average weight, and maintaining optimal growth and adiposity into adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…In a cohort of Australian men followed from birth, men born with gestational appropriate birth weights were significantly less likely to be grouped in the lowest quartile for their total motile sperm counts. Those men who were born preterm demonstrated reduced serum testosterone levels in adulthood, suggesting an adverse influence of growth restraint and prematurity on later life testicular function [41]. A prospective Danish birth cohort study of more than 2500 live born males found statistically significant associations between cryptorchidism and low birth weight, prematurity, being small for gestational age, substantial vaginal bleeding in pregnancy and breech presentation, which is in accordance with other studies [42].…”
Section: Potential Influences Of Male Reproductive Development and Pusupporting
confidence: 88%
See 3 more Smart Citations
“…In a cohort of Australian men followed from birth, men born with gestational appropriate birth weights were significantly less likely to be grouped in the lowest quartile for their total motile sperm counts. Those men who were born preterm demonstrated reduced serum testosterone levels in adulthood, suggesting an adverse influence of growth restraint and prematurity on later life testicular function [41]. A prospective Danish birth cohort study of more than 2500 live born males found statistically significant associations between cryptorchidism and low birth weight, prematurity, being small for gestational age, substantial vaginal bleeding in pregnancy and breech presentation, which is in accordance with other studies [42].…”
Section: Potential Influences Of Male Reproductive Development and Pusupporting
confidence: 88%
“…The first study to formally examine the association of maternal oestrogen exposure on male reproductive development was a longitudinal cohort study of almost 400 adult males. It found that sperm output in adulthood was inversely correlated with cord serum oestradiol and oestrone [41]. Furthermore it has been reported that oestrogenic chemical exposure can also cause cryptorchidism [9].…”
Section: Maternal Serum Oestrogensmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, testing whether such adult-onset disorders originate in fetal life is challenging in humans, as it requires "looking back in time" over 20 or more years (2,11). Consequently, the TDS hypothesis remains largely untested and unproven (12,13), although circumstantial supporting evidence from clinical studies has grown progressively (1,3,5,14,15). If the TDS hypothesis was proved correct, it would refocus research effort in humans toward identifying causal factors acting via the pregnant mother that might be preventable.…”
Section: Introductionmentioning
confidence: 99%